Multimodal Anatomy Teaching Pedagogy: Student’s Perception for Effective Teaching of Anatomy Curriculum - Ibrahim Khan, Rakhshinda Iram, Marina Khan, Parkha Afridi, Ayesha Karim, Shabana Kiran (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: There is still much disagreement over the most effective way to teach anatomy. This article has discussed the benefits of these instructional strategies. Nowadays, teaching anatomy primarily involves PowerPoint presentations. . As a result, the following article discusses the numerous teaching approaches and students input and suggestion in making anatomy lectures more interesting and easy. The purpose of this study was to ascertain whether the multimodal anatomy teaching methodology currently in use is viewed favorably and to identify the specific modalities that were considered to be most successful. Material and Methods: It was a cross sectional study conducted in two steps. Step one was carried out by distributing 250 questionnaires out of which 192 students participating by filling the questionnaires. The second step was dividing a class of 2ND year MBBS students in to 3 groups where group A was given a lecture in a teacher centered manner, Group B was student centered and Group C was a combination. Assessment was conducted in the end of the lecture and data was analyzed using SPPSS version 20. Results: students thought each way of teaching and learning is important but the best way of teaching was a multimodal teaching pedagogy. 93% thought that using a power point presentation with the use of white board teaching is the best method of teaching. Similarly the results of the assessment showed teacher-student interactive approach produced the highest mean score (mean=1.87), followed by the student-centered approach (mean=1.79), and the lowest mean score (mean=1.36) was recorded for the teacher-centered approach, according to the estimated marginal mean estimates based on the teaching method used. All three instructional approaches’ average estimates are within the 95% confidence intervals. The findings show that the most successful method for getting the highest test scores is a combination of teacher-centered and student-centered teaching techniques. This demonstrated that rather than the lecturer monopolizing the transfer of information to the learners, interaction between the teacher and students during the teaching and learning process motivates the students to seek knowledge. The student-centered approach’s predicted mean score (mean=1.79) was slightly lower than the teacher-student interactive approach’s. This suggests that using student-centered strategies is a successful teaching strategy. When compared to student-centered and teacher-student interactive techniques, the results of adopting teacher-centered strategies were significantly lower (mean=1.36). The most successful strategy to teach basic anatomy is to use a variety of pedagogical educational materials; students seem to learn more quickly and effectively when using multimodal and system-based strategies. Future research should focus on evaluating the applicability of new curricula and student views of integrated and multimodal teaching paradigms as well as these paradigms’ capacity to meet learning objectives. Conclusion: In order to determine the general level of the learner characteristics, learner analysis is a crucial stage. This study offers recommendations on how to create instructional objectives and choose the best ways to accomplish them. The findings of this study can be used to create educational plans and choose efficient anatomy teaching techniques. Keywords: Multimodal, Large group discussion, small group discussion, mini seminar, integration